REKONSTRUKSI PEMIKIRAN FIKIH: Suatu Gagasan Awal Mencairkan Kebekuan Fikih di Indonesia - Mustafa, Muhtadin Dg. (Institut Agama Islam Negeri (IAIN) Palu, 2011)
Abstract: Indonesia is a country whose population is majority Muslim. Thus, the aspects of sharia (Islamic law) should color the religiousity of Indonesian Muslims. However, the shariah is not something static, but rather something dinasmic as it always gets in contact with social aspects. In this context that the reactualization and reconstruction of Islamic jurisprudence should be continually performed. The reactualization of the Islmamic jurisprudence related to pragmatic values covering the daily life patterns of the Muslims while the reconstruction the Islamic jurisprudence thought more focuses on conceptual intellectuality values. Based on the relationship of the idea of reactualization and reconstruction of the Islamic jurisprudence can be concluded that the latter is an infrastructure, while the renewal is a means to realize the function of shariah (Islamic law) as a social control and social engineering.Kata Kunci: rekonstruksi pemikiran fikih, reaktulisasi fikih, syariat, mazhab